Refractive index matched, nearly hard polymer colloids. (28th June 2019) - Smith, Gregory N.; Derry, Matthew J.; Hallett, James E.; Lovett, Joseph R.; Mykhaylyk, Oleksander O.; Neal, Thomas J.; Prévost, Sylvain; Armes, Steven P.
Abstract : Refractive index matched particles serve as essential model systems for colloid scientists, providing nearly hard spheres to explore structure and dynamics. The poly(methyl methacrylate) latexes typically used are often refractive index matched by dispersing them in binary solvent mixtures, but this can lead to undesirable changes, such as particle charging or swelling. To avoid these shortcomings, we have synthesized refractive index matched colloids using polymerization-induced self-assembly (PISA) rather than as polymer latexes. The crucial difference is that these diblock copolymer nanoparticles consist of a single core-forming polymer in a single non-ionizable solvent. The diblock copolymer chosen was poly(stearyl methacrylate)–poly(2, 2, 2-trifluoroethyl methacrylate) (PSMA–PTFEMA), which self-assembles to form PTFEMA core spheres in n -alkanes. By monitoring scattered light intensity, n -tetradecane was found to be the optimal solvent for matching the refractive index of such nanoparticles. As expected for PISA syntheses, the diameter of the colloids can be controlled by varying the PTFEMA degree of polymerization. Concentrated dispersions were prepared, and the diffusion of the PSMA–PTFEMA nanoparticles as a function of volume fraction was measured. These diblock copolymer nanoparticles are a promising new system of transparent spheres for future colloidal studies.